The architecture of the 10‐23 DNAzyme and its implications for DNA‐mediated catalysis. (15th December 2022) - Borggräfe, Jan; Gertzen, Christoph G. W.; Viegas, Aldino; Gohlke, Holger; Etzkorn, Manuel
Abstract : Understanding the molecular features of catalytically active DNA sequences, so‐called DNAzymes, is essential not only for our understanding of the fundamental properties of catalytic nucleic acids in general, but may well be the key to unravelling their full potential via tailored modifications. Our recent findings contributed to the endeavour to assemble a mechanistic picture of DNA‐mediated catalysis by providing high‐resolution structural insights into the 10‐23 DNAzyme (Dz) and exposing a complex interplay between the Dz's unique molecular architecture, conformational plasticity, and dynamic modulation by metal ions as central elements of the DNA catalyst. Here, we discuss key features of our findings and compare them to other studies on similar systems. Abstract : DNAzymes are high precision catalysts assembled from short DNA sequences. The prominent RNA‐cleaving 10‐23 DNAzyme has eluded high‐resolution characterisation attempts for decades. A comprehensive integrated structural biology approach could now change this situation and revealed a surprising but efficient molecular architecture. This structural snapshot (a) elaborates on central aspects of the recent findings, (b) discusses their mechanistic implications and (c) compares the new findings to similar established RNA‐cleaving systems.